USING DISTANCE PHYSICAL EDUCATION IN ELITE CLASS SOCCER REFEREE TRAINING: A CASE STUDY - (:unkn) unknown (TURKISH ONLINE JOURNAL EDUCATIONAL TECH-TOJET, 2011)
The objective of this study is to present a model in the framework of Distance Education (DE), which suggests that a Distance Physical Education Program (DPEP) could be applied to those who are at various ages, in various geographical locations, and are working in various professions as part-time or full-time professionals. The use of DE in physical education with the support of education technologies and specialist systems provides significant opportunities. Through its flexible structure, DPEP partly or completely eliminates the restrictions encountered in traditional physical education programs, such as high costs, differences in age, geographical location and profession, and it provides solutions that are specific to an individual. The scope of this study comprises all of the referees who are employed in the Turkish Super League (34 top-class and high classification referees and 78 top-class and high classification assistant referees). The program was applied for two years (2 x 46 weeks in 2008-2009 and 2009-2010). In order to collect data, physical measurements were made at the beginning of the application, at the end of the first year and at the end of the second year of the application to assess referees' capabilities of endurance, speed, agility and recovery ability. The results were loaded into a database. Based on the test results, referees were submitted to individual and physical education programs via weekly e-mails. The outputs recorded by the referees during the application period with the support of specialist systems were submitted to the trainer every week. These were then entered into the training diary in the software on the computer, and were later subjected to assessment. At the end of the assessment process, referees were provided with feedback and the physical education continued without interruption. For the analysis and evaluation of the data, statistical techniques, such as descriptive statistics, one-way repeated measures and post hoc comparisons, were used. When the analysis results were evaluated, it was found that the endurance capabilities of referees and assistant referees significantly improved, which is a fact that can directly affect their professional proficiencies. The results of this study reveal that it is possible to conduct remote physical education in the scope of DE, by taking into account the individual differences and by including the support of suitable technology.
Keywords: Distance education; distance physical education; referees; education technologies; physical development; PROFESSIONAL-DEVELOPMENT; STUDENTS; PERFORMANCE; MANAGEMENT; TEACHERS; TESTS